PENGEMBANGAN SISTEM PENJADWALAN KULIAH MENGGUNAKAN ALGORITMA GENETIK (STUDI KASUS : PASCASARJANA UNIVERSITAS JAMBI) - Toscany, Afrizal Nehemia; Roestam, Rusdianto (Jurnal Manajemen Sistem Informasi, 2017)
Current scheduling classes at Jambi University graduate there are still some constraints such as the creation of a relatively long schedules, conflicting schedules and schedule that does not correspond to the time availability of the lecturers. Therefore, the author provides a solution in the form of lecture scheduling system using genetic algorithm with programming language PHP and the MySQL DBMS. For system development method that is used is the waterfall. Lecture Schedule result generated by a system that has been built is becoming more precision with the allocated hours of teaching, classroom and professors. From the test results can also be concluded that the implementation of genetic algorithms is in compliance with the need to support the process of scheduling, so that scheduling can be done more quickly